Akuisisi dan Budaya Knowledge Sharing - Nuril Kusumawardhani Soeprapto Putri (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Large companies which are experiencing barriers in innovation often take a radical step to acquire knowledge, namely acquisition. Though innovation is not the only reason, acquisition will result in the company wishes to achieve competitive advantage affected by the creation of ideas, creativity and innovation. The three points can be achieved more easily when the knowledge sharing within the organization / company runs well. However, the acquisition maybe impacts as a counter-attack for the knowledge sharing culture both in the acquisitor and and company which obtains the acquisition. Therefore, a key to succeed the acquisition is a sharing culture among individuals within a company that runs well or even better. Individuals from the acquisitor and those of the company that obtains the acquisition can adapt to each other and have confidence in order not to hinder them to share knowledge. This study discusses in detail the potential impacts of an acquisition upon a knowledge sharing culture in a company.